2009
DOI: 10.1016/j.pec.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of an intervention to reduce low literacy barriers in inflammatory arthritis management

Abstract: Objective Test the efficacy of educational interventions to reduce literacy barriers and enhance health outcomes among patients with inflammatory arthritis. Methods The intervention consisted of plain language information materials and/or two individualized sessions with an arthritis educator. Randomization was stratified by education level. Principal outcomes included adherence to treatments, self-efficacy, satisfaction with care, and appointment keeping. Secondary outcomes included health status and mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 10 publications
0
62
0
Order By: Relevance
“…The SLR showed that PE is provided in various modes; individual face-to-face-meetings,19 20 23 26 30 37 42 67–73 groups,24 25 28 34–36 38–41 74–79 a combination of the two27 29 49 50 80 and online 81–83. Category I evidence was found for individual counselling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLR showed that PE is provided in various modes; individual face-to-face-meetings,19 20 23 26 30 37 42 67–73 groups,24 25 28 34–36 38–41 74–79 a combination of the two27 29 49 50 80 and online 81–83. Category I evidence was found for individual counselling.…”
Section: Resultsmentioning
confidence: 99%
“…Trained patients were involved in, or delivered two SMPs,75 82 two online programmes82 83 and one patient-led interactive workshop 89. The remaining interventions were provided by one HP 18–20 23 27 29 34 35 37 40 42 49 67–71 74 80 86 87 97. Which professionals should be involved, and how many, will depend on the aim, the topic and the context for the education.…”
Section: Resultsmentioning
confidence: 99%
“…This was in contrary to a recent study which tested the effect of a motivational interviewing programme on medication adherence in RA patients and did not demonstrate any significant change to patient beliefs about medications or in improving medication adherence and this may be due to focusing on patient-related factors only 32 . Other interventional studies failed to improve medication adherence were reported 33,34 . Most of this interventions were educational depends on enhancing patient knowledge and understanding of their disease but education alone is insufficient to increase medication adherence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researchers in rheumatology have been studying literacy level of patients 12 , examining the materials they develop and use 13 , studying the match between the reading level of materials and the skills of the intended audiences 14 , exploring the influence of literacy on recruitment processes 15 , and evaluating efforts to improve care through attention to literacy 16 .…”
Section: Rheumatologymentioning
confidence: 99%